Exploring Continuous Auditing Solutions and Internal Auditing: A Research Note - Páll M. Ríkhardsson; Kishore Singh; Peter Best (Journal of Accounting and Management Information Systems (JAMIS), 2019)
Research Question: Organizations increasingly buy standardized continuous auditing solutions from vendors rather than develop their own. What opportunities lie in exploring the adoption, implementation and application of such solutions in the context of internal auditing? Motivation: Extant literature has not fully examined the implications of this development and there are several interesting unexplored research questions in this area. Idea: We develop a framework for examining continuous auditing as an information system solution and link this to internal auditing. Data: We employ existing literature as data and build on similar frameworks from ERP systems and AIS research. Findings: The findings of the paper are a series of research questions for examining this relationship as well as a proposal for using different theoretical perspectives and methodologies. Contribution: The contribution is a new perspective on continuous auditing research that could move this research area forward and link it to current developments in the field.
Keywords: M41; M42; 650; continuous auditing; continuous monitoring; internal audit; information systems